INCLUSIVE GROWTH AND HUMAN DEVELOPMENT IN IRAQ (2004-2022) REALITY AND SOLUTIONS - Assistant Prof. Dr. Nadia Mahdi Abdul-Qader (Scholar Express Journals, 2025)
This study aims to highlight the importance of inclusive growth and human development in economic and social fields. Given the relevance of this topic in addressing global economic challenges such as poverty, unemployment, income inequality, and wealth distribution, inclusive growth offers potential solutions. The study adopts a descriptive analytical approach to human development indicators. This type of growth focuses on equitably distributing the benefits of economic growth among all segments of society, particularly the poor, and utilizing economic resources effectively. Inclusive growth seeks to reduce social and economic gaps by providing equal opportunities and achieving balanced development across different regions and social groups. The study aims to diagnose the causes of low growth rates and propose solutions to address them, aiming to enhance human development indicators and ensure that all individuals have equal opportunities in education, health, and employment, as well as create a conducive environment for them. One of the key findings of the study is that having a clean environment free from corruption and providing favorable economic, political, and security conditions contribute to achieving high levels of human development in Iraq and promoting inclusive growth. This would help overcome barriers that might weaken the effectiveness of human development efforts and hinder the achievement of development goals. During the study period, human development faced challenges that hindered the achievement of its goals, particularly in the health and education sectors, which kept services below the required standards and made it difficult to meet development targets. Therefore, improving and providing services in the education and health sectors is a key objective to achieving the desired human development in Iraq. These services contribute significantly to high levels of inclusive growth by providing job opportunities and utilizing Iraq's economic and financial resources for the benefit of the poor and ensuring a fair distribution of resources between the wealthy and the poor.
Keywords: Inclusive Growth; Human Development